Effectiveness of Guided Imagery in Reducing Anxiety Among Mental Health Outpatients: A Pilot Study - Murni, Mayang; Darmawati; Marthoenis, Marthoenis (Queeva Publishing, 2025)
Background: Guided imagery is a promising non-pharmacological intervention for anxiety reduction, yet its use in outpatient mental health care remains limited. This study aimed to evaluate its effectiveness in reducing anxiety among patients with mental disorders. Methods: A randomized controlled trial was conducted with 68 participants assigned to intervention or control groups. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS-A). Data were analyzed using the Wilcoxon test for within-group and the Mann-Whitney test for between-group comparisons. Results: The intervention group showed a significant reduction in anxiety levels compared to the control group (p = 0.003). After the guided imagery intervention, 76.5% (26 of 34) of the intervention group had reduced anxiety, while the control group showed minimal change (p = 0.129). Outpatients visit frequency also increased post-intervention in the intervention group. Conclusion: Guided imagery is an effective and feasible intervention for reducing anxiety in outpatient mental health settings and can be integrated into standard care.